The Aspects and Limits of the Knowledge of Structure in Architectural Design Process - Majid Ahmadnejad Karimi; Mahdi Mahmoudi Kamelabad; Maryam Azimi (صفه)
An understanding of structural knowledge is an inevitable prerequisite for the process of form making and space creation, with the integration of creative, economic and buildable structures always an integral aspect of architecture. The understanding of structure takes a multifaceted knowledge, and it is important to know the right type of structure and the right degree of structural understanding for architects. Some researchers believe that an understanding of mechanical concepts alone is not enough, because spatial ideas and not mechanical principles are often the starting point for many designs; and hence the need to be familiar with the spatial aspect of structure. The main aim here is to investigate the multiple aspects of the architect’s role in structural design. The research starts with a descriptive-analytical study of the relations between various aspects and the way they interact to form a building—through case studies—and concludes with an explanation of how architects can influence the ways in which structural design is incorporated into design process.